Modulation and Pharmacology of the Mitochondrial Permeability Transition: A Journey from F-ATP Synthase to ANT - Andrea Carrer (MDPI AG, 2021)
The permeability transition (PT) is an increased permeation of the inner mitochondrial membrane due to the opening of the PT pore (PTP), a Ca2+-activated high conductance channel involved in Ca2+ homeostasis and cell death. Alterations of the PTP have been associated with many pathological conditions and its targeting represents an incessant challenge in the field. Although the modulation of the PTP has been extensively explored, the lack of a clear picture of its molecular nature increases the degree of complexity for any target-based approach. Recent advances suggest the existence of at least two mitochondrial permeability pathways mediated by the F-ATP synthase and the ANT, although the exact molecular mechanism leading to channel formation remains elusive for both. A full comprehension of this to-pore conversion will help to assist in drug design and to develop pharmacological treatments for a fine-tuned PT regulation. Here, we will focus on regulatory mechanisms that impinge on the PTP and discuss the relevant literature of PTP targeting compounds with particular attention to F-ATP synthase and ANT.